Implementation of an IoT-based Temperature and Humidity Monitoring System in the Physics Education Laboratory - Holis Angga Saputra; Ahmad Hardyan Isnaini; Rifki Rifaldy; Joni Wijaya Fathoni (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
Physics laboratories require stable environments for accurate experiments, as temperature and humidity fluctuations can affect results and damage equipment. This research aimed to implement an Internet of Things (IoT)-based system to monitor these conditions in the FKIP UNRAM Physics Education Laboratory. The experimental method involved designing a system using an ESP8266 microcontroller and a DHT 11 sensor, which was programmed with the Arduino IDE to send data to the ThingSpeak platform via Wi-Fi for analysis. Over three days of testing, the system recorded an average temperature of 30.78°C and an average relative humidity of 82.76%, successfully revealing clear diurnal patterns and documenting inter-day environmental variability. Implementing this IoT system proved effective for acquiring detailed and relevant ecological data, which is crucial for ensuring the quality and validity. Future developments are suggested, including the integration of real-time notifications, interactive dashboards, and automated trend analysis, to further enhance laboratory management.